Optimalisasi Pencapaian Hasil Belajar Matematika Melalui Model Pembelajaran Berbasis Proyek Bagi Siswa Kelas VII - Yuniar Ika Putri Pranyata; Nur Afifah Dwi Setiari; Trija Fayeldi (CONSISTAN (Jurnal Tadris Matematika), 2026)
Low mathematics learning outcomes of students remain a fundamental challenge that is often faced at the junior high school level, especially in grade VII. This condition requires the implementation of a more innovative, contextual, and student-centered learning model. This study aims to describe the optimization of mathematics learning outcomes through the implementation of project-based learning with data and diagram topics in grade VII MTs Badrussalam Indonesia. A descriptive qualitative approach was used using Classroom Action Research consisting of one cycle. The subjects of the study were 19 students of grade VII, selected based on preliminary observations that showed an average score of only 34.11, well below the minimum mastery criteria set. Data was collected through evaluation tests, observation of teacher and student activities, interviews, and documentation. Data analysis is carried out using interactive qualitative techniques that include data reduction, data presentation, and conclusion drawn. The results of the study revealed that teacher activity reached a percentage of 92.8% and student activity reached 87.1%, both of which met the predetermined success indicators. The results of the final evaluation test showed that 84.2% of students managed to achieve grades above the minimum mastery criteria, with a grade average of 83.4. These findings showed a remarkable improvement compared to the initial conditions before the intervention. As a result, project-based learning has been proven to be effective in optimizing the mathematics learning outcomes of junior high school students significantly and meaningfully.